A detailed picture of a protein–carbohydrate hydrogen-bonding network revealed by NMR and MD simulations. (8th September 2020) - Nestor, Gustav; Ruda, Alessandro; Anderson, Taigh; Oscarson, Stefan; Widmalm, Göran; Gronenborn, Angela M
Abstract: Cyanovirin-N (CV-N) is a cyanobacterial lectin with antiviral activity towards HIV and several other viruses. Here, we identify mannoside hydroxyl protons that are hydrogen bonded to the protein backbone of the CV-N domain B binding site, using NMR spectroscopy. For the two carbohydrate ligands Manα(1→2)Manα O Me and Manα(1→2) Manα(1→6)Manα O Me five hydroxyl protons are involved in hydrogen-bonding networks. Comparison with previous crystallographic results revealed that four of these hydroxyl protons donate hydrogen bonds to protein backbone carbonyl oxygens in solution and in the crystal. Hydrogen bonds were not detected between the side chains of Glu41 and Arg76 with sugar hydroxyls, as previously proposed for CV-N binding of mannosides. Molecular dynamics simulations of the CV-N/Manα(1→2)Manα(1→6)Manα O Me complex confirmed the NMR-determined hydrogen-bonding network. Detailed characterization of CV-N/mannoside complexes provides a better understanding of lectin-carbohydrate interactions and opens up to the use of CV-N and similar lectins as antiviral agents.